1991
DOI: 10.1007/bf01313476
|View full text |Cite
|
Sign up to set email alerts
|

Population differences in gonad and pyloric caeca cycles of the New Zealand seastarSclerasterias mollis (Echinodermata: Asteroidea)

Abstract: Date of final manuscript acceptance: September 24, 1990. Communicated by J.M. Lawrence, TampaAbstract. Inshore and offshore populations of Sclerasterias moll& (Hutton, 1872) were sampled on the outer continental shelf off the Otago Peninsula, New Zealand, and their nutritional and reproductive cycles are described from [1985][1986]. Histological changes in the gonads are generally typical of other asteroids. The gametogenic cycle takes 12 too. The gonad and pyloric caeca indices in both females and males had a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 17 publications
3
17
1
Order By: Relevance
“…8 b). Seasonal changes in the carbohydrate contents of the pyloric caeca of the two populations showed similar trends, which closely followed changes in the pyloric caeca index (see Barker and Xu 1991). The offshore population had consistently higher carbohydrate contents, with significant differences between the two populations in May, June, August, November (ANOVA, P<0.001) and December (ANOVA, P<0.05) 1985, and May, July and September, 1986 (ANOVA, P<0.001).…”
Section: Level and Content Of Carbohydratesupporting
confidence: 53%
See 2 more Smart Citations
“…8 b). Seasonal changes in the carbohydrate contents of the pyloric caeca of the two populations showed similar trends, which closely followed changes in the pyloric caeca index (see Barker and Xu 1991). The offshore population had consistently higher carbohydrate contents, with significant differences between the two populations in May, June, August, November (ANOVA, P<0.001) and December (ANOVA, P<0.05) 1985, and May, July and September, 1986 (ANOVA, P<0.001).…”
Section: Level and Content Of Carbohydratesupporting
confidence: 53%
“…Protein in the ovaries of Sclerasterias mollis was about twice that of carbohydrate and lipid during oogenesis, and over twice that of carbohydrate and lipid levels during Stage I (see Barker and Xu 1991 for definitions of reproductive stages), while protein levels of testes were more than twice the combined level of carbohydrate and lipid levels during spermatogenesis, and over three times that of carbohydrate and lipid levels during Stage 1. This indicates that protein is also a major constituent in the gonads of S. mollis', however its level is rather constant, with a slight increase during gonadal development.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…rubens. However, biochemical studies of the gonads and the pyloric caeca of S. mollis have shown that there were differences between sexes in biochemical components in the gonads but not inthepyloric caeca of this species Barker 1990d, Barker andXu 1991b). Generally, there is a resting stage in reproductive cycle of echinoderms following spawning (Boolootian 1966).…”
Section: Introductionmentioning
confidence: 94%
“…Observers of other asteroid species have noted that individuals with large gonads are sometimes associated with areas of high resource quality (Crump 1971, Barker & Xu 1991. For example, in New Zealand, the sea star Sclerasterias mollis had larger pyloric caecum and gonad indices at a site where scallops were the primary prey available than at a site where the diet consisted of gastropods and other small prey (Barker & Xu 1991). When Pisaster occur at sites with abundant mussels and barnacles, the blue mussel Mytilus trossulus is the dominant prey in the diet, whereas acorn barnacles are rarely consumed (Sanford 1999, see also Feder 1970.…”
Section: Study Systemmentioning
confidence: 99%